Peran Pengawas dalam Meningkatkan Mutu Guru Madrasah di MTs. Negeri 2 Aceh Tamiang - Ismail, Sulaiman; W, Sulaiman; Nur, Muhammad (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
One factor in the low quality of education is the need for more training for teachers in schools and madrasas. This is the task and role of supervisors in developing teachers to improve the quality of education. Therefore, the main focus of this research is to describe the role of supervisors in improving the quality of teachers in madrasas. This research is descriptive and qualitative, taking the location of MTs.Negeri 2 Aceh Tamiang is the research location. Data was collected using interviews and observations of supervisors and madrasa heads as key informants. "Data analysis is guided by Miles and Huberman's theory through data reduction and data presentation followed by conclusions or verification." The end of this paper concludes that supervisors improve teachers' quality at the MTs.Negeri 2 Aceh Tamiang madrasah has made optimal supervision efforts in the academic and managerial fields. It is proven that supervisors have assisted in improving teachers' abilities in preparing the administration of learning planning/guidance programs, implementing learning/guidance, and carrying out assessments of student learning outcomes. Meanwhile, the managerial sector has guided madrasa heads.